Single-cell transcriptomics combined with proteomics of intrathecal IgG reveal transcriptional heterogeneity of oligoclonal IgG-secreting cells in multiple sclerosis - Polak, Justyna; Wagnerberger, Johanna H.; Torsetnes, Silje Bøen; Lindeman, Ida; Høglund, Rune A. Aa.; Vartdal, Frode; Sollid, Ludvig M.; Lossius, Andreas (Frontiers in Cellular Neuroscience, 2023)
The phenotypes of B lineage cells that produce oligoclonal IgG in multiple sclerosis have not been unequivocally determined. Here, we utilized single cell RNA-seq data of intrathecal B lineage cells in combination with mass spectrometry of intrathecally synthesized IgG to identify its cellular source. We found that the intrathecally produced IgG matched a larger fraction of clonally expanded antibody-secreting cells compared to singletons. The IgG was traced back to two clonally related clusters of antibody-secreting cells, one comprising highly proliferating cells, and the other consisting of more differentiated cells expressing genes associated with immunoglobulin synthesis. These findings suggest some degree of heterogeneity among cells that produce oligoclonal IgG in multiple sclerosis.